Influence of phenological growth stages and meteorological parameters on leaf blight infestation of wheat in Gangetic plains of West Bengal - Davi, Hijam Meronbala; Mahapatra, Sunita; Dutta, Subrata; Das, Srikanta (Journal of Cereal Research, 2017)
Field experiment was conducted for 2012-13 and 2013-14 during winte season at Research Farm of BCKV, Nadia, West Bengal to study the distribution pattern of leaf blight pathogens on wheat at different phenological Zadokâ€™s growth stage (GS) and its interaction with various meteorological factors. The result showed that at seedling stage (GS 15), Alternaria alternata and Alternaria triticina caused maximum infection and continue upto GS49 and Curvularia lunata, other pathogens were noticed upto GS33. Whereas, major pathogen, Bipolaris sorokiniana infestation started at GS15 and gradually increase and reach to its maximum at GS91. The results pertaining to meteorological factors also demonstrated that increase in maximum temperature (Tmax), minimumtemperature (Tmin), bright sunsine hours (BSH) and Dew Point morning (DPmor) significantly decreased A. alternata infection. Increase in Tmax, Tmin and DPmor and DPeve reduced A.triticina infestation. Whereas infection of B. sorokiniana increased with increase in Tmax, Tmin, BHS and DPmor although RHmax and RHmin had a negative correlation with its growth. C. lunata and other pathogens showed no significant correlation with these meteorological factors except that RHmin significantly effect on disease progression.Â Doi.org/10.25174/2249-4065/2017/71803